Generation Z's Determinants for Using Online Food Delivery in Jakarta - Michael Christian; Suryo Wibowo; Sunarno Sunarno; Rima Melati; Fitriana Titis Perdini (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2023)
One of the Indonesia's leading online food delivery services is Shopee Food. It has competed with other big players. This application has caught the attention of users, even those from the Z generation, who are known for their easy-to-move characteristics and are close to technological applications but sensitive to user experience. This generation's convenience is influenced by many factors. This study analyzes the factors that influence attitudes and behavior for sustainable use of this application in Jakarta. Quantitative data is collected using a survey and questionnaire. This PLS-SEM modeling study shows that after using the service in this application, the user's hedonic motivation must be followed by comfort and usability. The user will evaluate the post-use usefulness of the previous experience to form an attitude toward the next perceived experience. Behavioral intentions toward sustainable use are encouraged. This study highlights the importance of usability and ease of use in determining user comfort. Generation Z does not easily form positive usage attitudes until the benefits of the next experience are the same or better.